The effect of femoral bone tunnel configuration on tendon-bone healing in an anterior cruciate ligament reconstruction: An animal study. Issue 5 (May 2018) - Sato, Y.; Akagi, R.; Akatsu, Y.; Matsuura, Y.; Takahashi, S.; Yamaguchi, S.; Enomoto, T.; Nakagawa, R.; Hoshi, H.; Sasaki, T.; Kimura, S.; Ogawa, Y.; et al.
Abstract : Objectives: To compare the effect of femoral bone tunnel configuration on tendon-bone healing in an anterior cruciate ligament (ACL) reconstruction animal model. Methods: Anterior cruciate ligament reconstruction using the plantaris tendon as graft material was performed on both knees of 24 rabbits (48 knees) to mimic ACL reconstruction by two different suspensory fixation devices for graft fixation. For the adjustable fixation device model (Socket group; group S), a 5 mm deep socket was created in the lateral femoral condyle (LFC) of the right knee. For the fixed-loop model (Tunnel group; group T), a femoral tunnel penetrating the LFC was created in the left knee. Animals were sacrificed at four and eight weeks after surgery for histological evaluation and biomechanical testing. Results: Histologically, both groups showed a mixture of direct and indirect healing patterns at four weeks, whereas only indirect healing patterns were observed in both groups at eight weeks. No significant histological differences were seen between the two groups at four and eight weeks in the roof zone (four weeks, S: mean 4.8sd 1.7, T: mean 4.5sd 0.5, p = 0.14; eight weeks, S: mean 5.8sd 0.8, T: mean 4.8sd 1.8, p = 0.88, Mann-Whitney U test) or side zone (four weeks, S: mean 5.0sd 1.2, T: mean 4.8sd 0.4, p = 0.43; eight weeks, S: mean 5.3sd 0.8, T: mean 5.5sd 0.8, p = 0.61, Mann-Whitney U test) . Similarly, no significant difference was seen in the maximum failure load between group S and group T at four (15.6sd 9.0N and 13.1sd 5.6N) or eight weeks (12.6sd 3.6N and 17.1sd 6.4N, respectively). Conclusion: Regardless of bone tunnel configuration, tendon-bone healing after ACL reconstruction primarily occurred through indirect healing. No significant histological or mechanical differences were observed between adjustable and fixed-loop femoral cortical suspension methods. Cite this article : Y. Sato, R. Akagi, Y. Akatsu, Y. Matsuura, S. Takahashi, S. Yamaguchi, T. Enomoto, R. Nakagawa, H. Hoshi, T. Sasaki, S. Kimura, Y. Ogawa, A. Sadamasu, S. Ohtori, T. Sasho. The effect of femoral bone tunnel configuration on tendon-bone healing in an anterior cruciate ligament reconstruction: An animal study. Bone Joint Res 2018;7:327–335. DOI: 10.1302/2046-3758.75.BJR-2017-0238.R2.